DUS Characterization of Okra (Abelmoschus Esculentus (L.) Moench) Genotypes through Qualitative Characters - MJ JADAV; CA BABARIYA; DS DESHMUKH (Seed Research, 2026)
The investigation was undertaken at the Sagdividi Farm, Department of Seed Science and Technology,College of Agriculture, Junagadh Agricultural University, Junagadh, during kharif 2021 to DUS characterize 23okra genotypes released for general cultivation in Gujarat at state level as well as at the National level in centralIndia based on the qualitative characters. Observations for twenty three okra genotypes were recorded for 14morphological and 2 seed characters. Okra genotypes were divided into two groups based on the colour of thestem: green (19 genotypes) and red (4 genotypes), while based on the intensity of the stem’s green colour, okragenotypes were grouped as light (20 genotypes) and medium (3 genotypes). All okra genotypes were divided intotwo groups based on the colour of the flower petals: cream (8 genotypes) and yellow (15 genotypes), whilegenotypes were divided into two groups based on the flower’s purple base petal colour: both side (18 genotypes)and inside (5 genotypes), while based on the fruit colour, okra genotypes were grouped as green (9 genotypes)and light green (11 genotypes). Based on the fruit surface between ridges, the 23 genotypes of okra were categorizedas flat (20 genotypes) and convex (3 genotypes). The okra genotypes were categorized as absent (12 genotypes)and weak (11 genotypes) based on the constriction of the basal region of fruits. The okra genotypes were dividedinto three groups based on fruit pubescence: weak (16 genotypes), medium (2 genotypes) and strong (5 genotypes),while okra genotypes were divided into three groups based on the shape of fruit apex: acute (15 genotypes),narrow acute (3 genotypes) and blunt (5 genotypes). All the 23 okra genotypes were having green colour betweenveins. The okra genotypes were divided into two groups: dark (18 genotypes) and medium (5 genotypes) basedon the intensity of colour between veins. The okra genotypes were divided into light green (20 genotypes) andpurple (3 genotypes) groups based on the colour of the leaf veins. Based on the depth of lobing, the genotypeswere grouped as shallow (10 genotypes) and medium (13 genotypes), while based on the serration of leaf blademargin, the genotypes were grouped as weak (2 genotypes), medium (20 genotypes) and strong (1 genotype).Based on the seed colour, the genotypes were grouped as brown (6 genotypes) and green (17 genotypes), whilebased on the seed hairiness, the genotypes were grouped as present (19 genotypes) and absent (4 genotypes).